Symbolic Meaning In Traditional Clothes Of Makassar - Jenab Hamid; Dahlia D. Moelier; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2023)
This research aims to describe the symbolic meaning in traditional clothes of Makassar through a semiotic study. This research is a research that uses qualitative descriptive methods with Charles Sanders Pierce's semiotic analysis. The objective of this research is what are the symbolic elements in traditional clothes of Makassar and what are the symbolic meaning in traditional clothes of Makassar. Data collection techniques in this research began with observation, in-depth interviews and documentation. The informants, who are considered experts in this research, are a traditional figure as well as historian of Makassar and Anrong Bunting (wedding makeup stylist). From the results of the research conducted, then revealed in traditional clothes of Makassar has certain symbolic elements that are very dependent on the social status and age of the wearers, namely in terms of types, shapes, materials, accessories, colors, and the way to use of sarong. Traditional clothes of nobles are interpreted in terms of accessories, the quality of materials made of silver and gold. For ordinary people are made of brass or bronze. And in terms of colors, green for noble daughters, red for teenage girls, deep red for married women, purple for widows, white for caregivers, and black for the elderly or those aged 40 years. The symbolic meaning of the way to use sarong in Makassar man is as a symbol of etiquette, and for women it is a symbol of authority. The meaning in traditional clothes of Makassar for man and women is a symbol of honor and majesty. While the meaning of the accessories worn by Makassar man and women is the symbolize manners and as a symbol of personality, honesty, and harmony.